Inquiry-Based Instruction and Students’ Conceptual Mastery in Junior High School Mathematics: Basis for a Contextualized Instructional Enhancement Program in Eastern Tabuk District III, Kalinga - Contis, May; Sabado, Adriano (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined inquiry-based instruction and students’ conceptual mastery in junior high school mathematics in Eastern Tabuk District III, Tabuk City, Kalinga, during School Year 2025-2026. It determined students’ perceptions of inquiry-based instruction in terms of student engagement, critical thinking and problem-solving, collaboration and communication, use of real-world applications, and teacher facilitation and support. It also assessed students’ conceptual mastery and analyzed the relationship between the two variables. The study used a descriptive-correlational design with 200 junior high school students from Grades 7 to 10 selected through stratified random sampling. Data were gathered through a structured questionnaire and treated using weighted mean and Pearson correlation. Results showed that students agreed that inquiry-based learning was evident in engagement, critical thinking, collaboration, and real-world applications, while teacher facilitation and support was rated strongly agreed. Students also demonstrated a high level of conceptual understanding. All inquiry-based learning domains were positively and significantly related to conceptual understanding, with real-world applications having the strongest relationship. The study concludes that inquiry-based instruction strengthens meaningful mathematical learning when supported by guided facilitation, collaborative tasks, and authentic problem situations. A contextualized instructional enhancement program is proposed to improve students’ conceptual mastery in mathematics.
Keywords: Conceptual Mastery, Inquiry-based Instruction, Instructional Enhancement, Junior High School Mathematics, Real-world Applications